Analysing the Representation of Minorities In Governance and Decision making Processes Under Modi's Administration (London Journal of Research In Humanities and Social Sciences, 2024)
This research paper examines the representation of minorities, particularly the Muslim community, in governance and decision-making processes under the administration of Prime Minister Narendra Modi in India. Through a comprehensive literature review and empirical analysis, it delves into the historical context, theoretical frameworks, and methodologies employed. The paper scrutinises Modi's administration's policies and their impact on religious and ethnic minorities, highlighting concerns over marginalisation and discrimination. It assesses decision-making structures and mechanisms, emphasising the exclusion of minority voices. Furthermore, it explores the implications of minority representation on governance, drawing parallels with international studies. Overall, the paper underscores the importance of equitable representation for minority groups in fostering inclusive governance and enhancing social cohesion.
Keywords: Gender; domestic violence; Violence; Intersectionality; femicide; fundamental rights; positive obligations; family life; Nation; narration; Morocco; theatre; inception; aspects.; Anthropolinguistics; Weton; semiology; governance; Minority representation; Decision-making processes; Narendra Modi administration; Political power; Religious minorities; Ethnic minorities